Human cumulus cell sensitivity to vitrification, an ultrastructural study. Issue 3 (3rd July 2018) - Taghizabet, Neda; Khalili, Mohammad Ali; Anbari, Fatemeh; Agha-Rahimi, Azam; Nottola, Stefania Annarita; Macchiarelli, Guido; Palmerini, Maria Grazia
Summary: Cumulus cells (CCs) play an important role in the regulation of female gamete development, meiotic maturation, oocyte–sperm interaction, capacitation and acrosome reaction. However, their role in maintaining oocyte competence after vitrification is unclear as controversial data on their protecting action against oocyte cryoinjuries are available. Here we described the effects of vitrification on the ultrastructure of human CCs collected from women undergoing assisted reproductive technologies (ARTs). In total, 50 patches of CCs, sampled from high-quality human cumulus–oocyte complexes, were randomly allocated into two groups after patient informed consent: 1, fresh CCs (controls, n = 25); 2, vitrified CCs ( n = 25). Samples were then prepared and observed by transmission electron microscopy. In fresh CCs, in which small cell clusters were visible, cell membranes were joined by focal gap junctions. Microvilli were rare and short. Nuclei, mitochondria, smooth endoplasmic reticulum (SER), Golgi apparatus and lipid droplets appeared well preserved; vacuoles were scarce. After vitrification, we observed two populations of CCs: light CCs, with a smooth appearance and few short microvilli; and dark CCs, with numerous and long microvilli. In both, most of the organelles appeared similar to those of fresh CCs. Lipid droplets were denser and more numerous, with respect to fresh CCs. They were mainly located in the peri-nuclear and sub-plasmalemmal regions. Numerous packed electron-negative vacuoles were visible. The vitrification procedure did not cause alterations in the fine structure of major organelles, except for an increased amount of lipid droplets and vacuoles. This specific sensitivity of human CCs to vitrification should be considered during ARTs.